Duração de aleitamento materno exclusivo em mães adolescentes atendidas em uma unidade de referência de Belo Horizonte-MG - Cecy Maria Lima Santos (2009)
The study about the exclusive breastfeeding period at teenager mothers showed at literature is shorter. Is known that, the exclusive breastfeeding, must to be maintained at least until the first six months of age and must be continuous until two years old or more considering that, this is the adequate nutritional source to the children, which help them to create the vinculum between mother and son, so important to this range of age. This study, target to verify how long the breast feeding is maintained by the teenager mother attended on the reference work. On this study, we have evaluated 103 mothers with age between 12 to 18 years old and 11 months, by using the validated questionnaire, which was done by the longitudinal study. The duration of the exclusive breast feed, was found as been 130 days. During this study, we have observed that, the babys mothers which use the pacifiers have 1,78 times more change to interrupt the feeding if its compared to the others one. Over than that, the mothers which have been started the prenatal by fourth months of gestation have 1,53 times more chance of interrupt the breast feed if compared with the others one which started the prenatal by the third month of gestation. The others factors such as smoking, married stage, kind of delivery, social economic stage between them, didnt have a statistical significance on this study, despite of the influence of this on the period of exclusive breast feeding. The duration of exclusive breastfeeding on this population, considering the average of the duration, was better than the study showed on the literature, despite of lower than the recommendation by WHO. So, the implantation of reference center to attendant the teenager is one important strategic which can help the promotion and incentive to the breastfeeding.